Optimizing Jigsaw Type of Cooperative Learning Model to Improve Students' Mathematical Self-Confidence - Guntur, Muhamad Ikhsan Sahal; Anggraini, Seftika; Rosnawati, Raden (Mandalika Mathematics and Educations Journal, 2020)
This research is motivated by the low self-confidence of students in the learning process at SMAN 1 Ngemplak where the students who were respondents were 35 students consisting of 22 female students and 13 male. The solution given is using a cooperative learning model with jigsaw type. Based on the evaluation of cycle I obtained an average value of 61.71 with a percentage of mastery learning 57%. The highest score obtained by students is 80 and the lowest score is 40. Whereas for giving a confidence questionnaire in pre-cycle is 66.63 ÃÂ in the medium category and after cycle I it increases to 80.17 but still in the medium category. The results obtained in the first cycle are still quite good or have not been fulfilled. Based on the results of the second cycle evaluation, the average is obtained 75.57 and 89% completeness learning increased from 57% previously. In addition, an increase in student confidence was also seen from the comparison of the results of the assessment questionnaire in pre-cycle, cycle I and cycle II, which initially 66.63 became 80.17 and ended 86.80.ÃÂ Abstrak Penelitian ini dilatar belakangi oleh rendahnya kepercayaan diri siswa dalam proses pembelajaran di SMAN 1 Ngemplak dimana siswa yang menjadi responden adalah 35 siswa yang terdiri dari 22 siswa perempuan dan 13 laki-laki. Solusi yang diberikan adalah menggunakan model pembelajaran cooperative learning tipe jigsaw. Berdasarkan evaluasi siklus I diperoleh nilai rata-rata 61,71 dengan persentase ketuntasan belajar 57%. Skor tertinggi yang diperoleh siswa adalah 80 dan skor terendah adalah 40. Sedangkan skor kepercayaan diri pada pra siklus adalah 66,63 yang berada pada kategori sedang. Setelah dilakukan siklus I, skor kepercayaan diri meningkat menjadi 80,17 tetapi masih dalam kategori sedang. Berdasarkan hasil evaluasi siklus II, diperoleh nilai rata-rata 75,57 yang sebelumnya adalah 61,71. Ketuntasan belajar pada akhir siklus II adalah 89% yang meningkat dari 57% pada akhir siklus I. Selain itu, peningkatan kepercayaan diri siswa juga terlihat dari perbandingan hasil angket penilaian pada pra siklus, siklus I dan siklus II, yang awalnya 66,63 menjadi 80,17 dan berakhir 86,80.ÃÂ ÃÂ